Peran Kearifan Lokal dalam Pemberdayaan Masyarakat: Studi Kasus Masyarakat Adat Sasak di Desa Sade, Kabupaten Lombok Tengah - Ardiansyah, Lalu Muhammad; Rizky Hidayat, Lalu (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study analyzes the role of local wisdom in empowering the Sasak Indigenous community of Sade Village, Central Lombok Regency. Local wisdom is defined as a set of values, norms, and social practices that guide community life and are passed down across generations. The study uses a qualitative case study approach. Data were collected through participant observation, in-depth interviews with customary leaders and community members, and analysis of relevant documents. The data were analyzed thematically to examine the relationship between local wisdom and community empowerment. The results show that local wisdom plays an important role in strengthening social cohesion, regulating social behavior, and supporting community autonomy. Customary institutions such as awig-awig, banjar, and besiru function as effective social control mechanisms based on collective agreement and shared values. Principles of mutual cooperation, respect for customary rules, and harmony with nature encourage sustainable resource management and social resilience. Local wisdom also supports value-based education, cultural identity preservation, and community adaptation to change, including tourism development. This study concludes that local wisdom is a key social and cultural resource for empowering indigenous communities. Its integration into community-based development is essential to ensure cultural continuity, social sustainability, and inclusive local development.